Function and functionality in the conceptual design process - Zadnik, Žiga (Strojniški vestnik, 2009)
In order to contribute to functional modeling of product based on the functional synthesis paradigm, the work sets out to present criteria for the product functions and functionalities' definition. The product function matrix and their requests model has been generated that interrelates functions and technical systems. Functions are described in terms of parameters defined from physical laws. Through winning parameters correlation elements in the product function matrix and their requests are defined that interrelate functions and the technical systems which solve them. Winning parameters are derived from a set of parameters for each function thus they are of major importance and have the strongest impact on a given function. By the application of the product function matrix and their requests in the conceptual design process the designer can reexamine his or her work through comparison of the possibilities of realization of new ideas based on previously made products.
Keywords: razvoj izdelkov; funkcionalnost; modeliranje; matrike